Factors Influencing Changes in Consumer Behavior in Choosing Coffee Outlets in Jakarta During the Covid-19 Pandemic - Andhalia Liza Marie; Tri Djoko Sulistyo; Heny Ratnaningtyas (At-Tadbir : jurnal ilmiah manajemen, 2022)
This study aims to determine the perception of health risks, innovation capabilities, and coffee shop atmosphere on changes in consumer behavior during the Covid-19 pandemic. This study uses a descriptive quantitative approach. The number of samples is 100 respondents, and the sampling technique is purposive sampling—data collection techniques using online questionnaires. The research locations were in five coffee shops: Tak Kie Coffee, Sun Ho Coffee, Djie Coffee, Bakoel Koffie Coffee, and Gondangdia Luwak Coffee. The results showed that the perception of health risks and the atmosphere of the coffee shop had a significant positive effect on changes in consumer behavior. In contrast, innovation capability harms changes in consumer behavior. The dominant result is the atmosphere of the coffee shop, which has a t-count that is greater, 7.259, than the t-table of 1.960 and a significant value is 0.000. This is because coffee shops carry out health protocols such as distance restrictions, maintaining cleanliness, good air circulation, and the availability of outdoor facilities. Coffee shops should maintain health protocols, and visitors should be limited so that consumers can feel safe and comfortable. They should also be able to make coffee while traditionally not selling coffee online so that the aroma and taste are maintained properly and do not change from the original.